Negotiating Taboo, Culture, and Science: Culturally Responsive Science Learning for Reproductive Health Literacy of Elementary School Teacher Candidates in Papua - Aisyah Ali; Akhmad Kadir (Jurnal Penelitian Pendidikan IPA, 2026)
Reproductive health literacy in Papua still faces various socio-cultural challenges, such as body taboos, customary norms, and religious values ​​that limit open discussion about reproduction. These conditions also impact prospective elementary school teacher students who will later serve as health educators for children. This study will investigate how prospective teacher students negotiate taboos, culture, and scientific knowledge in culturally responsive science learning to develop reproductive health literacy. The study used a narrative inquiry approach involving five of 28 fifth-semester students in the Elementary School Teacher Education (PGSD) Study Program in Papua. Data were collected through in-depth narrative interviews, weekly reflective journals, and participant observation, then analyzed using Clandinin's three-dimensional narrative framework (temporality, sociality, and place). The results of the study indicate a process of transformation from taboo body language to meaningful scientific language, negotiation between indigenous knowledge, religion, and science, the formation of the class as a safe space for dialogue, and the development of students' professional identities as prospective health educators. These findings confirm that culturally responsive science learning not only enhances cognitive understanding but also plays a significant role in strengthening reproductive health literacy and pedagogical readiness of prospective elementary school teachers in Papua.